Laparoscopic hepatectomy for hepatocellular carcinoma in a patient with congenital factor V deficiency: a case report - Takaomi Seki; Mariko Tsukagoshi; Norifumi Harimoto; Kenichiro Araki; Akira Watanabe; Norihiro Ishii; Kei Hagiwara; Kouki Hoshino; Ryo Muranushi; Satoru Kakizaki; Yoshiyuki Ogawa; Hiroshi Handa; et al. (Surgical Case Reports, 2022)
Abstract Background Factor V (FV) deficiency is an extremely rare disease, with an incidence of 1 in 1 million. The bleeding symptoms are mild, and the prognosis is good; however, the safety of surgical treatment is unclear, because there are few available reports. Herein, we report a case of hepatocellular carcinoma with congenital FV deficiency in a patient who safely underwent laparoscopic hepatectomy. Case presentation A 79-year-old man, diagnosed with hepatocellular carcinoma of liver segment 5, with type C cirrhosis and sustained virological response visited our hospital. He had congenital FV deficiency, and blood tests showed coagulation deficiencies with an FV activity of < 2.6%, prothrombin time activity of 11%, and activated partial thromboplastin time of 100.3 s. Surgery and radiofrequency ablation were considered for treatment. Since the tumor was in contact with the Glissonean pedicle 5 + 6, surgery was judged to be superior from the viewpoint of safety and curability. After discussing the safety of the surgery with a hematologist, it was determined that the operation could be performed safely by transfusing sufficient fresh frozen plasma (FFP). Laparoscopic hepatic segment 5 + 6 subsegmental resection was performed with FFP transfusion, fluid restriction, airway pressure control, and central venous pressure reduction to control the bleeding. Bleeding was minimized during the transection of the liver parenchyma and no bleeding tendency was observed. The operative time was 445 min, and the amount of intraoperative bleeding was 171 mL. No complications, such as postoperative bleeding, were observed, and the patient was discharged on the eighth postoperative day. Conclusions Liver surgery can be performed safely in FV-deficient patients with strict coagulation capacity monitoring and appropriate transfusion of FFP. Preoperative evaluation of cardiac function to determine tolerance to high doses of FFP and ingenuity of surgery and intraoperative management to minimize blood loss are important.